Students’ understanding in airborne transmission of sars-cov-2 by dynamic fluid perspective using structure of observed learning outcomes (solo) taxonomy - Bagus Helmeyanto; Eko Hariyono (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika)
Online learning imposed by government as an impact of the COVID-19 pandemic affected students’ ability to understand the authentic problem. Authentic problem used to train students’ ability to apply their knowledge in physics. This research mainly discusses about the students' levels understanding of the authentic problem that is SARS-CoV-2 airborne transmission using the SOLO taxonomy. This research used a descriptive qualitative approach using eight questions related to SARS-CoV-2 airborne transmission. Data collected via online survey platform and analyzed by calculating the percentage of student's level of understanding for each given question. The result shown that 59% student included in pre-structural level, 19% included in uni-structural level, 10% included in multi-structural level, 3% included in relational level, and 10% included in extended-abstract level.